Identification of fertility-related genes for maize CMS-S via Bulked Segregant RNA-Seq - Xiner Qin (PeerJ, 2020)
Cytoplasmic male sterility (CMS) is extensively used in maize hybrid production, and identification of genes related to fertility restoration for CMS is important for hybrid breeding. The fertility restoration of S type CMS is governed by several loci with major and minor effects, while the mechanism of fertility restoration for CMS-S is still unknown. In this study, BSR-Seq was conducted with two backcrossing populations with the fertility restoration genes, Rf3 and Rf10, respectively. Genetic mapping via BSR-Seq verified the positions of the two loci. A total of 353 and 176 differentially expressed genes (DEGs) between the male fertility and male sterile pools were identified in the populations with Rf3 and Rf10, respectively. In total, 265 DEGs were co-expressed in the two populations, which were up-regulated in the fertile plants, and they might be related to male fertility involving in anther or pollen development. Moreover, 35 and seven DEGs were specifically up-regulated in the fertile plants of the population with Rf3 and Rf10, respectively. Function analysis of these DEGs revealed that jasmonic acid (JA) signal pathway might be involved in the Rf3 mediated fertility restoration for CMS-S, while the small ubiquitin-related modifier system could play a role in the fertility restoration of Rf10.